Impact of Bony Pelvis Type on Mode of Delivery in Reproductive Age Females of District Rahim Yar Khan: A Cross-Sectional Analysis - Masood, Solmaz; Aman, Sadia; Bushra, Hira; Wahid, Hamna; Ahsan, Aneela; Faisal, Sanober (Journal of Neonatal Surgery, 2025)
Background: Among the bony elements of human body, the pelvis always gained importance due to its intricate structure as well as due to its important functional role in childbirth and locomotion.[1] X-ray pelvimetry is being used to determine the type of bony pelvis and its predictive role in mode of delivery in the females. Pelvises can be classified as Gynecoid, android, anthropoid, and platypelloid pelvis. Gynecoid type favors normal birth process but rest of the types hinders natural birth variably depending on their bony morphology, which leads to poor delivery outcomes and need of C-section. Objective: To Assess the impact of different bony pelvic types on the mode of delivery among reproductive-age females in District Rahim Yar Khan using X-ray pelvimetry. Study Design: Cross sectional study Study Setting: Department of Gynecology & Obstetrics and Department of Radiology, Sheikh Zayed Hospital ,Rahim Yar Khan from May 2024 to October 2024. Methods: The subjects for this study were recruited from the Department of Gynecology & Obstetrics, sheikh Zayed hospital, Rahim Yar Khan. The females who were admitted in Gynae ward and labor room for spontaneous vaginal delivery and caesarian section were sent to the radiology department for x-ray pelvimetry. X-ray pelvimetry was done in erect posture in both AP and lateral views. On the basis of which type of pelvis was determined. Later on association of type of bony pelvis with mode of delivery, was observed. Statistical analysis was performed using the Chi-square test; a p-value <0.05 was considered significant. Results: Data was collected among 384 postpartum females, mean. The majority of 146 (38.0%) had gynecoid pelvis and was most compatible with vaginal delivery, followed by, android pelvis 96 (25.0%), anthropoid pelvis 84 (22.0%) and platypelloid pelvis 58(15.0percent). Conclusion: Pelvic Morphology, as classified by X-ray pelvimetry, Significantly impacts delivery mode. Pelvic type assessment may aid obstetricians in predicting delivery outcomes and planning labor management